Mangan tamu express integrating the culinary culture of Pampanga to the Clark hi-speed express rail station - Santos, Kheiro E.; Madrid, Dolores Cecilia (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
This thesis seeks to explore the impact that architecture can have on peoples’ relationship with food and its accompanying effects in raising the awareness of people to Pampanga’s culinary tourism. The concept of this thesis is that rail station can be designed in such way that it incorporates the cultural specialty of its regional context thereby help improve the awareness of people to the specific regional specialty.
I chose a site on the vicinity of Clark International Airport to locate my project, the Mangan Tamu Express Rail Station and Culinarium. This site is ideal for bringing people and food together as it is between the Clark International Airport and the proposed Second Central Business District of Clark. In addition to being near the vicinity of Angeles, Pampanga the centre of food commerce in Pampanga. The Rail station- Culinarium complex combines the rail transport function of the rail station, a small-scale food processing facilities for producers with a market place and restaurants for consumers. Providing an environment in which these ever-distancing demographics can interact would help reduce the gap between people and food. The goal of this thesis is to design a building that fosters a meaningful and productive connection to food consumption by bringing people closer to its source.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Food vendors; Rail stations -- Pampanga